2020
DOI: 10.1111/ijmr.12242
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Competitive Advantage: A State‐of‐the‐Art Literature Review and Research Directions

Abstract: In many industries, the traditional sources of competitive advantage tend to evaporate fairly rapidly. Therefore, managers need to continually rethink and reformulate their firm strategies. Likewise, scholars have felt compelled to shift the traditional centre of attention from competitive advantage that is sustainable over time to a focus on how firms compete by achieving a series of temporary advantages. However, the proliferation of research on temporary competitive advantage, far from building a solid body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 338 publications
(442 reference statements)
2
63
0
1
Order By: Relevance
“…Using the resource-based view recent empirical studies have applied the TCA framework to reveal the temporary nature of resource advantages, and they have highlighted the importance of acquiring new resources (Dagnino et al, 2008(Dagnino et al, , 2020Huang et al, 2015;Li and Liu, 2014). Firms can achieve SCA if they have resources that are valuable, rare, imperfectly imitable and irreplaceable, and they can achieve TCA if their resources are only valuable and rare.…”
Section: Tca Framework and Environmental Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the resource-based view recent empirical studies have applied the TCA framework to reveal the temporary nature of resource advantages, and they have highlighted the importance of acquiring new resources (Dagnino et al, 2008(Dagnino et al, , 2020Huang et al, 2015;Li and Liu, 2014). Firms can achieve SCA if they have resources that are valuable, rare, imperfectly imitable and irreplaceable, and they can achieve TCA if their resources are only valuable and rare.…”
Section: Tca Framework and Environmental Dynamicsmentioning
confidence: 99%
“…In the era of increasingly complex and rapid technological innovation, firms find it difficult to maintain sustainable competitive advantage (SCA) (Dagnino et al, 2020); hence, they conduct extensive scientific collaborations with external organizations to obtain new scientific and technological knowledge (Huang et al, 2015;Li and Liu, 2014;Klein et al, 2020). In particular, they collaborate with universities and research institutions (URIs) to develop advanced industrial technologies (Lin, 2019;Petruzzelli and Murgia, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Since the firm’s competitive environment has become more global, uncertain, and aggressive, firms need to constantly enhance their knowledge base in order to perform well (Dagnino et al, 2021). To tackle this need, firms usually take advantage of their competencies in familiar and consolidated technological knowledge (Kuo et al, 2019) to exploit their knowledge and offer new products or services (Peeters and Martin, 2017).…”
Section: Linking Purpose‐led Approaches To Randd Management Literature In Relation To Health Emergencies Response: a Conceptual Frameworkmentioning
confidence: 99%
“…Although definitions differ across studies, as shown in --------------Table 1 about here --------------Temporary advantage. The most frequently identified dimension is temporary competitive advantage (for a recent review of the literature on temporary advantages see Dagnino et al (2020)). In the theory of hypercompetition, D'Aveni (1994) questions the well-known view of sustainable competitive advantages and argues that "today's strengths become tomorrow's weaknesses so quickly that sustaining advantages is nearly impossible" (1994: p. 6), as the environment constantly changes.…”
Section: Research On Hypercompetition: Emergence Of the Fieldmentioning
confidence: 99%